Influence of the driving frequency and equivalent parameters on displacement amplitude of electrostatic linear comb actuator - Kien, Hoang Trung; Ham, Vu Cong; Phuc, Pham Hong (Vietnam Journal of Mechanics, 2018)
A new method determining the equivalent dynamic parameters such as stiffness, vibrating mass, and air damping factor in motion direction of shuttle (i.e. in y-direction) is proposed, thence the differential motion equation of shuttle is established and solved to achieve a typical displacement formula. Simulation and experimental results show that the change of ELCA’ displacement is inappreciable while the range of driving frequency up to 27 Hz (error of 10% with driving voltage is a square wave). Moreover, the range of driving frequency for the ELCA can be extended up to 1 kHz with displacement amplitude error of 10% while the shape of driving voltage is a harmonic sine wave.